2021
DOI: 10.1111/ajgw.12512
|View full text |Cite
|
Sign up to set email alerts
|

Effect of microoxygenation on acetaldehyde, yeast and colour before and after malolactic fermentation on Pinot Noir wine

Abstract: Background and Aims Microoxygenation (MOX) is widely used in winemaking. Its impact, however, on Pinot Noir wines has not been well documented. We investigated the influence of MOX on colour parameters and on the anthocyanin and polymeric pigment concentration of a young Pinot Noir wine. The relationship between MOX, yeast growth and acetaldehyde production was also explored. Methods and Results Microoxygenation was applied before or after malolactic fermentation (MLF), and at two oxygen doses [10.8 and 52.4 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(28 citation statements)
references
References 63 publications
2
24
2
Order By: Relevance
“…Recently, we have demonstrated that MOX applied to a young Pinot noir wine led to an increase in colour intensity (with a higher absorbance at 520 nm) and tannin concentration, and a higher oxygen dosage favoured the formation of polymeric pigments (Yang et al, 2021a;Yang et al, 2021b). At the same time, a higher percentage of galloylated tannins but fewer trihydroxylated tannins were found after MOX, indicating a negative impact on astringency perceptions (Yang et al, 2021a;Yang et al, 2021b).…”
Section: Introductionmentioning
confidence: 94%
See 4 more Smart Citations
“…Recently, we have demonstrated that MOX applied to a young Pinot noir wine led to an increase in colour intensity (with a higher absorbance at 520 nm) and tannin concentration, and a higher oxygen dosage favoured the formation of polymeric pigments (Yang et al, 2021a;Yang et al, 2021b). At the same time, a higher percentage of galloylated tannins but fewer trihydroxylated tannins were found after MOX, indicating a negative impact on astringency perceptions (Yang et al, 2021a;Yang et al, 2021b).…”
Section: Introductionmentioning
confidence: 94%
“…Recently, we have demonstrated that MOX applied to a young Pinot noir wine led to an increase in colour intensity (with a higher absorbance at 520 nm) and tannin concentration, and a higher oxygen dosage favoured the formation of polymeric pigments (Yang et al, 2021a;Yang et al, 2021b). At the same time, a higher percentage of galloylated tannins but fewer trihydroxylated tannins were found after MOX, indicating a negative impact on astringency perceptions (Yang et al, 2021a;Yang et al, 2021b). However, Yang et al (2021b), attributed the decrease in trihydroxylated tannins to Saccharomyces cerevisiae activity, as MOX had also induced yeast growth (Yang et al, 2021a), where the proliferation and autolysis of this yeast species have been shown to affect tannin composition through adsorption to the cell walls (Mazauric and Salmon, 2005;Mekoue Nguela et al, 2015).…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations